Setting the agenda for American archaeology : the National Research Council archaeological conferences of 1929, 1932, and 1935 - O'Brien, Michael J. (Michael John), 1950-; Lyman, R. Lee (Classics in southeastern archaeology., 2001)
A Dan Josselyn Memorial Publication This collection elucidates the key role played by the National Research Council seminars, reports, and pamphlets in setting an agenda that has guided American archaeology in the 20th century. In the 1920s and 1930s, the fascination that Americans had for the continent's prehistoric past was leading to a widespread and general destruction of archaeological evidence. In a drive toward the commercialization of antiquities, amateur collectors and ""pot hunters"" pillaged premier and lesser-known sites before the ar